The Influence of Asset Intensity, Employee Intensity, and Intellectual Capital on the Competitiveness of Manufacturing Industries: Cost Stickiness as a Mediating Variable - Yeni Kusmiyati; Wiwik Utami (Green Publisher Indonesia, 2024)
The low competitiveness of the Indonesian manufacturing industry is a current phenomenon causing a decline in Indonesia's manufacturing industry competitiveness ranking below that of Singapore, Malaysia, and Thailand. This indicates that Indonesia needs to enhance four factors: national economic performance, policy efficiency, business efficiency, and infrastructure. The purpose of this research is to examine the influence of factors affecting competitiveness. The data analysis technique used in this research is multiple linear regression analysis. The population in this study is companies listed on the Indonesian stock exchange. Data collection used purposive sampling method, with a total sample size of 212, with a sampling quota of 109 companies that have both sales increases and decreases annually. In this study, there are independent variables such as Asset Intensity, Employee Intensity, and Intellectual Capital, dependent variable Competitiveness, and mediating variable Cost Stickiness. The results of the research show that the variables of employee intensity and intellectual capital have an influence in this study, whereas asset intensity does not have an influence in this study. Additionally, Cost Stickiness has not been able to mediate the influence on Asset Intensity, Employee Intensity, and Intellectual Capital.